Strategies for Developing Students’ Life Skills through the Ulama Cadre Proficiency Standards (SKKU) at Madrasah Aliyah Almaarif Singosari Malang - Khusna, Nur Jazah Anil; Nasih, Ahmad Munjin; Afifulloh, M. (ISLAMIKA, 2025)
This study analyzes the strategy for developing students’ life skills through the implementation of the Ulama Cadre Proficiency Standard (SKKU) at Madrasah Aliyah Almaarif Singosari, Malang. The research focuses on how SKKU is designed, implemented, and evaluated within the framework of Islamic education to support the growth of students’ cognitive, personal, and social competencies. Employing a descriptive qualitative approach, data were gathered through observation, in-depth interviews, questionnaires, and documentation. Findings reveal that SKKU curriculum development is grounded in national education policies such as Permendiknas and KMA 183, integrated with local institutional directives. Its implementation involves continuous teacher professional development, the provision of facilities for religious practices, and the use of motivational strategies to engage students. Evaluation is conducted progressively daily, monthly, semesterly, and annually addressing both academic performance and practical life skill acquisition. Key challenges identified include low student motivation, limited teacher capacity for consistent monitoring, and insufficient parental involvement. Despite these obstacles, the study concludes that the SKKU approach significantly contributes to the holistic development of students’ life skills. It emphasizes the importance of coordinated collaboration among educational institutions, families, and communities to maximize outcomes in character-based and life skill-oriented Islamic education.